Geopolitik: Energi persaingan dan kerja sama di era modern - Putra, Iffan Efendi (Maliki Interdisciplinary Journal, 2026)
Energy is a fundamental element driving economic expansion, the industrial sector, and transportation systems, as well as supporting the standard of living of contemporary civilization. The urgency of this resource’s availability has transcended the economic dimension, transforming it into a crucial instrument in the international political constellation. The current phenomenon of energy geopolitics has emerged as a vital discourse reflecting the contestation between countries over access to resources, while simultaneously triggering collaborative initiatives to ensure sustainable energy distribution. This exploration analyzes the mechanisms of competition and synergy in the energy sector in the modern era, identifies the determinants influencing energy geopolitics, and evaluates its implications for global economic stability. By applying a desk study methodology through a review of scientific literature and international reports, the study results indicate that global powers tend to exploit energy as a means of political diplomacy and economic domination. Nevertheless, cross-border integration, both regionally and globally, remains an absolute prerequisite for achieving energy security and accelerating the transition to renewable energy utilization..